Vehicular connectivity algorithm for cooperative transportation systems. (September 2022) - Sharma, Mayank; Kumar, Pradeep; Tomar, Ranjeet Singh
Abstract: Vehicular Ad-hoc Network (VANET) means connectivity between wireless interface and mobile vehicle equipment which could be of either homogeneous or heterogeneous nature. VANET is an emerging part of research due to its ability to create intelligent transport systems. Roadside fixed equipment (RSU), and on-board unit (OBU) can be either public means of transport service providers or private (belonging to companies or individuals). In this infrastructure, messages flow from vehicle to vehicle and vehicle to roadside via wireless technologies such as IEEE 8.02.11.P and IEEE 1609 WAVE. The main issue in VANET implementation is the design of routing topology that gives accurate vehicle-to-vehicle transmission. In VANET, every participating vehicle node works as a single-vehicle node or wireless router, allowing vehicles that are 100–500 m far from creating a network and connected to each other by a large range using dynamic source routing (DSR) protocol. In this paper, we focus on improving connectivity by integrating simulation of urban mobility (SUMO) with NETSIM and present a new algorithm for packet delivery in different dense environments. In this work, we propose a vehicle connectivity algorithm for less (40), moderate (50), and more (60) number of vehicles and also analyze the threshold value of successfully delivered packets through simulation and the proposed algorithm. In the simulations and proposed method, the overall link and application throughput in VANET is enhanced, and the outcome shows that the connectivity is better than in the other techniques. This study has achieved good throughput in a dense vehicle environment. Performance of the networks has been measured through throughput, delay, packet delivery ratio (PDR), overhead head transmission for less (40), moderate (50), or more (60) number of vehicles on different road paths.